Enzymatic determination of L(-)malic and L(+)lactic acids in wine by flow injection analysis - Lima, José L. F. C. (2011)
The enzymatic determination of L(-)malic and L(+)lactic acids in several types of wines by flow injection analysis (FIA) with spectrophotometric detection is described. This flow injection system, which incorporates a dialysis unit for adjusting the composition of the injected solutions to the requirements of the measuring system, enables determinations of these two organic acids without the need for any prior treatment of the wine samples, with a concentration interval of between 0.02 and 4 g/L, and a sampling rate of approximately 20 determinations per hour. The results obtained with this FIA method for various types of Portuguese wines are in good agreement with those of the batch method which uses the same enzymatic technique and are quite precise as they present a coefficient of variation below 2.5%.